2012
DOI: 10.1074/jbc.m112.394353
|View full text |Cite
|
Sign up to set email alerts
|

Dynein Light Chain 1 (LC8) Association Enhances Microtubule Stability and Promotes Microtubule Bundling

Abstract: Background: Dynein Light Chain 1 (LC8) has been shown to pull down tubulin subunits, suggesting that it interacts with microtubules. Results: LC8 decorates microtubules in vitro and in Drosophila embryos, promotes microtubule assembly, and stabilizes microtubules both in vitro and in tissue-cultured cells. Conclusion: LC8 stabilizes microtubules. Significance: Data provide the first evidence of a novel MAP-like function of LC8.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 69 publications
1
31
0
Order By: Relevance
“…For instance, several kinesins whose sole function was thought to be to carry the cargo have now been shown to regulate microtubule dynamics independently of their motor functions (39). Recently, LC8, a light chain of cytoplasmic dynein, has been found to promote tubulin polymerization and to stabilize interphase microtubule network in cells (40). In another study, it was shown that ␣TAT1, an ␣-tubulin acetyltransferase, destabilizes microtubules and accelerates microtubule dynamics in mammalian cells (41).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, several kinesins whose sole function was thought to be to carry the cargo have now been shown to regulate microtubule dynamics independently of their motor functions (39). Recently, LC8, a light chain of cytoplasmic dynein, has been found to promote tubulin polymerization and to stabilize interphase microtubule network in cells (40). In another study, it was shown that ␣TAT1, an ␣-tubulin acetyltransferase, destabilizes microtubules and accelerates microtubule dynamics in mammalian cells (41).…”
Section: Discussionmentioning
confidence: 99%
“…However, the best-documented function of dynein is its role in retrograde transport of membranous organelles within neuronal cells (Schroer et al, 1989;Schnapp and Reese, 1989). Dynein is required in the maintenance of microtubules (Asthana et al, 2012) and is involved in lysosomal (Lin and Collins, 1992) and endosomal vesicular transport mechanisms (Aniento et al, 1993). Autophagosomal movement within the cell for efficient lysosomal encounters is also dependent on the dynein-dynactin motor complex (Kimura et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The significance of the interaction of Astrin and LC8 has not been resolved. LC8 functions to enhance mitotic spindle (2). Localization of LC8 to kinetochore is regulated by Astrin (29), collectively suggesting that Astrin may regulate spindle stability by targeting LC8 to kinetochore.…”
Section: Discussionmentioning
confidence: 98%
“…For example, Astrin can guide the kinetochore targeting of its interaction proteins cytoplasmic linker-associated protein-1␣ (CLASP-1␣), dynein light chain 8 (LC8), and SKAP (14,29). The interaction of Astrin with the SKAP and CLASP-1␣ is required for chromosome alignment and segregation, spindle stabilization, and silencing of the spindle assembly checkpoint (2,14,25). Besides, interaction of Astrin with polo-like kinase 1 (PLK1) or Aurora-A is also important for the microtubule organization and spindle pole integrity (40), and the binding of Astrin to sensitive-to-nitrogen mustard 1B (SNM1B) has been reported to be essential for the prophase checkpoint (22).…”
mentioning
confidence: 99%